Der Franziszeische Kataster im Kronland Österreichisch- Schlesien (1821-1851) - Scharr, Kurt (2023)
The Franzican Cadastre was a most successful attempt of the Habsburg monarchy to organize its lands with regard to land valuation and taxation into a uniform legal space. With the help of a proven methodology and on a broad basis of social, economic and social history, for the first time a comprehensive source edition is presented here for Austrian Silesia.